Efficient In Vitro Micropropagation Of Purple Fleabane (Vernonia Anthelmintica Willd.): A Multipurpose Under-Exploited Oil-Yielding Herb. - SHAHNAZ SUBHAN; VEENA AGRAWAL (International Journal of Pharma and Bio Sciences, 2011)
Micropropagation of Vernonia anthelmintica, an important medicinal and under exploited oil-yielding herb of asteraceae has been achieved through seedling cotyledonary node explants. The explants if reared on Murashige and Skoog’s (MS) medium supplemented with 0.1, 1, 5 and 10 µM levels of cytokinins, viz. N6-benzyladenine (BA), kinetin (Kn), N6-(2-isopentenyl) adenine (2iP) either alone or in combinations with auxins i.e. α-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) or an adjuvant like adenine sulphate (Ad.S.), or coconut water (CW) induced direct multiple shoots in their axils. The best response was evoked on 5 µM BA in combination with 5% CW added to MS medium where cent percent cotyledonary nodes differentiated an average of 4.5±0.7 shoots per explant. The excised shoots rooted best in half strength MS basal medium with 2% sucrose. Nearly 75% shoots organized an average of 1.9±0.5 roots per shoot within 12 days. An early induction of in vitro flowering has also been noticed in 33.3% cultures with 5% CW and 5 µM BA within six weeks. The tissue culture derived plantlets were successfully acclimatized to field with 60% survival. Thus, for the first time, a reliable method for efficient regeneration and achieving early flowering and fruiting, in an economically important crop has been developed.